Laparoscopic versus open mesh repair of unilateral inguinal hernia: a comparative study - P. B., Sudarshan; B. S., Sundaravadanan; V. P., Kaarthik; S., Prabu Shankar (International Surgery Journal, 2017)
Background: Inguinal hernia repair is now one of the most commonly performed general surgical procedures in practice. Laparoscopic inguinal hernia repair was started in year 1999 and since then has gained popularity over the last 2 decades. The introduction of a laparoscopic technique has sparked a debate in the literature over the superiority of this method versus open repair. Even though for bilateral and recurrent inguinal hernias, laparoscopic approach is recommended, there is not enough literature to recommend its routine use in unilateral inguinal hernia repair. Methods: A randomised prospective study was conducted at a tertiary care teaching hospital, comparing both Laparoscopic inguinal hernia repair and lichensteins tension free mesh repair as treatment modalities for unilateral inguinal hernia. Total number of patients in the study group was 60. Patients who were willing for the study were selected for the open or laparoscopic procedure in a randomised way. Open procedure was done by 2 senior surgeons and laparoscopic procedure was performed by 2 other senior surgeons at associate professor designation. Various parameters like the complication rate, post-operative pain, post-operative stay and time to return to work were analysed. Results: Out of the 60 patients, 30 patients underwent open inguinal hernia repair and another 30 patients underwent Laparoscopic inguinal hernia repair. The mean age group was 46.73 in open surgery group and 42.10 in laparoscopic group. 23.3% of the patients in open hernioplasty developed seroma, hematoma in the post-operative period. Whereas 10% had seroma collection in laparoscopic group. No incidence of recurrence in both the groups. No significant difference in pain score between both the groups during immediate post-operative period on POD 0, however there was significant difference in pain score on POD 3 (mean pain in open group 4.13 and lap group 2.87) and POD 7(mean pain in open group 2.90 and lap group 1.23). Mean duration of stay in hospital for open hernioplasty was 7.8 days and for Laparoscopic hernioplasty was 3.07 days. Mean duration of return to work in open hernioplasty was 14.37 days and in laparoscopy group was 9.13 days. Conclusions: There are potential benefits for laparoscopic inguinal hernia repair over lichtenstein’s repair for unilateral inguinal hernias in terms of post-operative pain, hospital stay and early return to work.